Eroding the Common Law Paradigm for Creation of Property Interests and the Hidden Costs of Law Reform - David M. Becker (Washington University Law Quarterly, 2005)
At the core of property, its ownership, and its concepts, is real estate. Indeed, most of property law has been forged and shaped by the law of real property. Because land lasts forever and so does its history, the marketplace could not function without clarity and stability as to ownership. The last twenty-five to thirty years have, however, produced relatively rapid and even staggering changes in the law of property. Among them is § 2-707 of the Uniform Probate Code (hereinafter referred to as § 2-707). This article focuses and expands upon this transcendent impact. It elaborates how § 2-707 has made a major change in the common law paradigm for creation of property interests. This article predicts that the changes imposed by § 2-707—and any others it might spawn—will inevitably create serious problems because these changes impair a system of expression that is logically sound and has worked successfully for many centuries. In conclusion, it sounds a warning about all law reform and its hidden dangers, especially law reform which reflects the views of a select group, that alters the way lawyers must think, design, and draft.
Keywords: Common law; Property law reform; Trust beneficiaries; Probate law & practice; Estate planning; Legal composition; Legal reform; Property rights; United States